An investigation of the DC and RF performance of InP DHBTs transferred to RF CMOS wafer substrate *Project supported by the National Natural Science Foundation of China (No. 61331006) and the Natural Science Foundation of Zhejiang Province (No. Y14F010017). (May 2018) - Ren, Kun; Zheng, Jiachen; Lu, Haiyan; Liu, Jun; Wu, Lishu; Zhou, Wenyong; Cheng, Wei
Abstract: This paper investigated the DC and RF performance of the InP double heterojunction bipolar transistors (DHBTs) transferred to RF CMOS wafer substrate. The measurement results show that the maximum values of the DC current gain of a substrate transferred device had one emitter finger, of 0.8 μ m in width and 5 μ m in length, are changed unobviously, while the cut-off frequency and the maximum oscillation frequency are decreased from 220 to 171 GHz and from 204 to 154 GHz, respectively. In order to have a detailed insight on the degradation of the RF performance, small-signal models for the InP DHBT before and after substrate transferred are presented and comparably extracted. The extracted results show that the degradation of the RF performance of the device transferred to RF CMOS wafer substrate are mainly caused by the additional introduced substrate parasitics and the increase of the capacitive parasitics induced by the substrate transfer process itself.